Broadly Applicable Z‐ and Diastereoselective Ring‐Opening/Cross‐Metathesis Catalyzed by a Dithiolate Ru Complex1. Issue 7 (29th January 2014) - Koh, Ming Joo; Khan, R. Kashif M.; Torker, Sebastian; Hoveyda, Amir H.
Abstract A broadly applicable Ru‐catalyzed protocol for Z‐selective ring‐opening/cross‐metathesis (ROCM) is disclosed. In addition to reactions relating to terminal alkenes of different sizes, the first examples of Z‐selective ROCM processes involving heteroaryl olefins, 1, 3‐dienes, and O‐ and S‐substituted alkenes as well as allylic and homoallylic alcohols are reported. Z‐Selective transformations with an α‐substituted allylic alcohol are shown to afford congested Z alkenes with high diastereoselectivity. Transformations are performed in the presence of 2.0–5.0 mol % of a recently disclosed Ru‐based dithiolate complex that can be easily prepared in a single step from commercially available starting materials. Typically, transformations proceed at ambient temperature and are complete within eight hours; products are obtained in up to 97 % yield, >98:2 Z/E, and >98:2 diastereomeric ratio. The present investigations reveal a mechanistically significant attribute of the Ru‐based dithiolates that arises from electrostatic interactions with anionic S‐based ligands.